(untitled) (International Journal of Innovative Technologies in Economy, 2024)
The urgency of this research is focused on Mina Padi Integrated Agriculture education in order to increase rice production and freshwater fish production by Cibahayu Village farmers as well as digital marketing training in the creative economy of making fish-based culinary that has high economic value, as well as digital-based marketing education so as to increase economic opportunities from these marketing strategies. Through this research activity, it is hoped that digital literacy related to production marketing can be a provision in utilizing existing economic opportunities. The purpose of this research activity is to provide experience and knowledge for farmers to be able to carry out the mina padi system, besides that the community is able to apply the creative economy by making fish-based culinary, and understand the digital-based production marketing process.